Ionization of aqueous cations: photoelectron spectroscopy and ab initio calculations of protonated imidazole - Jagoda-Cwiklik, Barbara; Slavícek, Petr; Nolting, Dirk; Winter, Bernd; Jungwirth, Pavel (The journal of physical chemistry. B, 2008)
Photoelectron spectroscopy and ab initio calculations employing a nonequilibrium polarizable continuum model were employed for determining the vertical ionization potential of aqueous protonated imidazole. The experimental value of 8.96 eV is in in excellent agreement with calculations, which also perform quantitatively for ionization of aqueous alkali cations as benchmark species. The present results show that protonation of imidazole increases its vertical ionization potential up in water by 0.7 eV, which is significantly larger than the resolution of the experiment or the error of the calculation. This combined experimental and computational approach may open the possibility for quantitatively analyzing the protonation state of histidine, of which imidazole is the titratable side chain group, in aqueous peptides and proteins.